The impact of supplementary service towards customer satisfaction / Ramli Saad, Wan Shahrul Aziah Wan Mahamad and Yong Azrina Ali Akbar - Saad, Ramli; Wan Mahamad, Wan Shahrul Aziah; Ali Akbar, Yong Azrina (Universiti Teknologi MARA, Kedah, 2024)
In the very competitive business environment of today, achieving customer satisfaction is crucial for companies seeking long-term success. Businesses need to deliberately bring on additional services in addition to their core offerings in order to meet increasingly dynamic customer demand. By increasing use and improving its value and offer, supplemental services elevate the basic product (Nafei & EL-Horany, 2021). While core product offers are important, it is impossible to underestimate the impact of supplementary services on various customer needs. Given that customers have a lot of options, businesses need to go above and beyond to meet and surpass their expectations. Because of these value-added services, customers have a more positive and memorable experience, which increases their satisfaction. The supplementary services, which function as a value-added service for the product, play important roles in affecting the consumers’ purchase decisions (Zheng et al., 2022). Because of today's very competitive business environment, companies are always looking for ways to gain the upper hand over their rivals. These days, consumers' demands might not be met by goods and services alone. As a result, additional services are becoming a vital tool for companies to compete in the market. Therefore, companies could strategically implement supplementary services as one of the effective methods of enhancing customers’ satisfaction.